Akumulasi Mikroplastik Pada Bivalvia di Ekosistem Manggrove Desa Tanah Mea Kabupaten Donggala - Yesika, Veronika; Nurdin, Musdalifah; Rauf, Abd.; Zainal, Syech; Bustamin, Bustamin; Sabran, Moh. (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aimed to identify bivalve species with high microplastic content and the types of microplastics present in those bivalves within the mangrove ecosystem of Desa Tanah Mea, Donggala Regency.Â A quantitative descriptive method was used. Sampling locations were determined using purposive sampling, divided into two stations: Station I, a mangrove ecosystem adjacent to a residential area, and Station II, a mangrove ecosystem near the coastline. Bivalve samples were collected using the hand collection method, with 10 individuals per species.Â Subsequently, bivalve tissues were processed, and microplastic content was analyzed. Data analysis involved counting the number and types of microplastics from the field samples using an abundance formula. Results showed that Polymesoda erosa, found at Station I, contained 22.2 microplastic particles per individual, comprising 104 fragments, 22 films, 92 fibers, and 4 foams.Â Anadara granosa, found at Station II, contained significantly fewer microplastics, with 2.5 particles per individual, consisting of 12 fragments, 5 films, and 8 fibers. Polymesoda erosa was the bivalve species with the highest microplastic content, with fragments, films, fibers, and foams identified.Â Therefore, bivalves can serve as bioindicators for assessing microplastic pollution levels in the mangrove ecosystem of Desa Tanah Mea, Donggala Regency.